Self‐Powered Tactile Sensor Array Systems Based on the Triboelectric Effect. (10th December 2018) - Tao, Juan; Bao, Rongrong; Wang, Xiandi; Peng, Yiyao; Li, Jing; Fu, Sheng; Pan, Caofeng; Wang, Zhong Lin
Abstract: With the arrival of intelligent terminals, tactile sensors which are capable of sensing various external physical stimuli are considered among the most vital devices for the next generation of smart electronics. To create a self‐powered tactile sensor system that can function sustainably and continuously without an external power source is of crucial significance. An overview of the development in self‐powered tactile sensor array system based on the triboelectric effect is systematically presented. The combination of multi‐functionalization and high performance of tactile sensors aimed at achieving highly comprehensive performance is presented. For the tactile sensor unit, a development is summarized based on the two primary modes which are vertical contact–separation and single‐electrode. For the pressure mapping array, the resolution is significantly enhanced by the novel cross‐type configuration based on the single‐electrode mode. Integrated with other mechanisms, the performance will be further elevated by broadening of the detect range and realizing of visualization of pressure imaging. Then, two main applications of human–machine interaction (HMI) and trajectory monitoring are comprehensively summarized. Finally, the future perspectives of self‐powered tactile sensor system based on triboelectric effect are discussed. Abstract : Recent advancements in and perspectives on self‐powered tactile sensor array systems based on the triboelectric effect are systematically summarized. The tactile sensor unit and array from the combination of high performance and multifunctionality are described, and based on which, numerous self‐powered system applications especially in the human–machine interface and trajectory monitoring are highlighted.